Efficacy of Non-Pharmacological Interventions to Prevent and Treat Delirium in Older Patients: A Systematic Overview. The SENATOR project ONTOP Series - Abraha, Iosief; Trotta, Fabiana; Rimland, Joseph M.; Cruz-Jentoft, Alfonso; Lozano-Montoya, Isabel; Soiza, Roy L.; Pierini, Valentina; Dessì Fulgheri, Paolo; Lattanzio, Fabrizia; O’Mahony, Denis; Cherubini, Antonio (PloS one, 2015)
Non-pharmacological intervention (e.g. multidisciplinary interventions, music therapy, bright light therapy, educational interventions etc.) are alternative interventions that can be used in older subjects. There are plenty reviews of non-pharmacological interventions for the prevention and treatment of delirium in older patients and clinicians need a synthesized, methodologically sound document for their decision making. We performed a systematic overview of systematic reviews (SRs) of comparative studies concerning non-pharmacological intervention to treat or prevent delirium in older patients. The PubMed, Cochrane Database of Systematic Reviews, EMBASE, CINHAL, and PsychINFO (April 28th, 2014) were searched for relevant articles. AMSTAR was used to assess the quality of the SRs. The GRADE approach was used to assess the quality of primary studies. The elements of the multicomponent interventions were identified and compared among different studies to explore the possibility of performing a meta-analysis. Risk ratios were estimated using a random-effects model. Twenty-four SRs with 31 primary studies satisfied the inclusion criteria. Based on the AMSTAR criteria twelve reviews resulted of moderate quality and three resulted of high quality. Overall, multicomponent non-pharmacological interventions significantly reduced the incidence of delirium in surgical wards [2 randomized trials (RCTs): relative risk (RR) 0.71, 95% Confidence Interval (CI) 0.59 to 0.86, I2=0%; (GRADE evidence: moderate)] and in medical wards [2 CCTs: RR 0.65, 95%CI 0.49 to 0.86, I2=0%; (GRADE evidence: moderate)]. There is no evidence supporting the efficacy of non-pharmacological interventions to prevent delirium in low risk populations (i.e. low rate of delirium in the control group)[1 RCT: RR 1.75, 95%CI 0.50 to 6.10 (GRADE evidence: very low)]. For patients who have developed delirium, the available evidence does not support the efficacy of multicomponent non-pharmacological interventions to treat delirium. Among single component interventions only staff education, reorientation protocol (GRADE evidence: very low)] and Geriatric Risk Assessment MedGuide software [hazard ratio 0.42, 95%CI 0.35 to 0.52, (GRADE evidence: moderate)] resulted effective in preventing delirium. In older patients multi-component non-pharmacological interventions as well as some single-components intervention were effective in preventing delirium but not to treat delirium.